2020
DOI: 10.1371/journal.pone.0238346
|View full text |Cite
|
Sign up to set email alerts
|

What does the American public know about child marriage?

Abstract: Global efforts to eradicate 'child marriage' (<18 years) increasingly target governments, the private sector and the general public as agents of change. However, understanding of child marriage may be subject to popular misconceptions, particularly because of ambiguity in the age threshold implied by the term 'child', and because awareness campaigns routinely emphasize extreme scenarios of very young girls forcibly married to much older men. Here, we ascertain public knowledge of child marriage via an online s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Other studies have also found that US women who marry before age 18 or 19 have greater risk of subsequently developing poor mental health [ 56 ] and chronic conditions [ 57 ]. The notion that girl child marriage represents a unique phenomenon that must be examined and understood separately from marriage among women aged 18 or older is supported by our findings, those of previous studies [ 53 , 56 , 57 ], and the exceptional context of marriage before age 18 in the US [ 23 , 58 ]. Given that marrying at a young age is associated with marital instability [ 5 , 53 , 56 ] and that high early fertility can limit maternal education and labor opportunities [ 59 ], married mothers below age 18 and their children may be particularly vulnerable to future adverse health outcomes [ 56 , 57 ] and socioeconomic hardships [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other studies have also found that US women who marry before age 18 or 19 have greater risk of subsequently developing poor mental health [ 56 ] and chronic conditions [ 57 ]. The notion that girl child marriage represents a unique phenomenon that must be examined and understood separately from marriage among women aged 18 or older is supported by our findings, those of previous studies [ 53 , 56 , 57 ], and the exceptional context of marriage before age 18 in the US [ 23 , 58 ]. Given that marrying at a young age is associated with marital instability [ 5 , 53 , 56 ] and that high early fertility can limit maternal education and labor opportunities [ 59 ], married mothers below age 18 and their children may be particularly vulnerable to future adverse health outcomes [ 56 , 57 ] and socioeconomic hardships [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…Given that marrying at a young age is associated with marital instability [ 5 , 53 , 56 ] and that high early fertility can limit maternal education and labor opportunities [ 59 ], married mothers below age 18 and their children may be particularly vulnerable to future adverse health outcomes [ 56 , 57 ] and socioeconomic hardships [ 53 , 54 ]. Public knowledge regarding child marriage is very limited in the US [ 58 ], and little research has been conducted on the topic domestically [ 5 , 7 ], but as most states permit marriage below age 18 [ 8 ], it is critical to understand the extent of the health and social implications of child marriage in the country. Our study contributes to addressing this important knowledge gap, but additional work using longitudinal designs is required to examine other health and social indicators in relation to child marriage and the underlying pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The forced marriage narrative is indeed central to the global health concept of child health. The terms child and forced marriage are commonly used interchangeably reflecting the legal view that minors inherently cannot give informed consent [ 13 ], and imagery commonly depicts marriages of young people as forced ( Fig 1 ; see also [ 15 ]). Yet, forced marriages rarely featured in lived experiences of adolescent marriage, with the exception of one attempted forced marriage which notably the participant refused in a demonstration of her agency.…”
Section: Discussionmentioning
confidence: 99%
“…Campaign narratives routinely highlight relatively extreme scenarios, e.g. prepubescent girls forced to marry much older men by their parents [ 15 ]. Ultimately, female marriage under 18-years is seen as a lynchpin in a complex system of inequalities, which if eliminated, will lead to an improved quality of life and health for AGYW [ 16 ].…”
Section: Introductionmentioning
confidence: 99%